Investigation of heat sink layer Ag thickness-dependent time-resolved lattice dynamics in FePt/Ag heat assisted magnetic recording media - Xu, D.B. (2014)
2012 Digest APMRC - Asia-Pacific Magnetic Recording Conference: A Strong Tradition. An Exciting New Look!